SEXUAL EDUCATION AND TEACHING AT SCHOOL INCLUSION: SOCIAL COMMITMENTS OF SCIENCE TEACHING - Pena, Andreia Lelis; Caixeta, Juliana Eugênia; Mól, Gerson de Souza (Cadernos de Educação Tecnologia e Sociedade, 2019)
Science Education must assume its social commitment to Sexual Education and Inclusion, because it is responsible for the elaboration of pedagogical contexts that enable the construction of scientific concepts related to body and sexuality. In order to do so, science education must position human sexuality as a complex phenomenon, whose teaching must consider biological, psychological and social phenomena, and contemplate diversity as inherent in human groups. In this work, we seek to investigate the perception of Science teachers about Sexual Education and the understandings about the sexuality of students with specific needs, in inclusive schools of the Federal District. The relevance of this research is anchored in three aspects: first, the invisibility of the theoretical and methodological discussion that articulates sexuality and disability; according to the repercussion of this invisibility in the non-teaching and; third, in the possibilities of initial and continued training of science teachers in the subject matter. It was a qualitative investigation whose information was generated through semi-structured interviews with eight teachers and analyzed with the support of WQDA software. The teachers' perceptions about the sexuality of people with disabilities, outlined in this research, showed advances on the one hand, that is, on the recognition of many teachers that people with disabilities are subjects of desire; but also stagnation, when there are still teachers who have not been able to recognize their sexuality or how to act in the classroom in order to approach different ways of being and living together, considering sexuality. The analyzes presented reveal the importance of planning proposals for initial and continuing training for Science teachers, with a view to meeting the social commitments of Science Education towards inclusive and sexual education, which implies in defending and promoting the essential right to education person to human development in its entirety, including sexuality and its teaching, in a plural and bio-social perspective.